IMAM SYAFI'I'S PERSPECTIVE ON DEBT SETTLEMENT WITH PARKING LAND MANAGEMENT RIGHTS ASSURANCE (Case Study of Medan Perjuangan, Medan City) - Rambe, Rachmat Husein; Zahara, Fatimah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The Medan Perjuangan community has a practice of disputed debts, but they are unable to pay off these debts, so they provide guarantees in the form of parking space rights as collateral for their debts. The purpose of this research is to respond to the author's main problem formulation, which is the settlement of debt disputes with guaranteed rights to manage parking areas from the perspective of Imam Syafi'i. In this study, a qualitative method was used to analyze Imam Syafi'i's perspective and how Islamic law views debt settlement transactions with guaranteed rights to manage parking lots in Medan's battlefield. According to the findings of this study, in Medan Perjuangan, Medan City, debtors with good intentions to settle their credits can settle their disputes over problematic receivables amicably, and the method used to settle these debts is seen as better than other alternative settlements by providing guarantees in the form of parking space rights in battlefield because the debtor does not have the ability to pay off.